HUBUNGAN PENERAPAN PROTOKOL KESEHATAN PANDEMI COVID 19 DENGAN KEPATUHAN PEDAGANG MENGGUNAKAN MASKER DI PASAR DELI TUA TAHUN 2022 - VIKTOR EDYWARD MARBUN (Jurnal Penelitian Kesmasy, 2022)
The COVID-19 pandemic is the spread of the 2019 coronavirus disease worldwide. The disease is caused by a new type of corona virus named SARS-Cov-2. And it was declared a pandemic by the World Health Organization (WHO) on March 11, 2020. The outbreak of this corona virus is almost all over the world, including in Indonesia. Using of the masks during the Covid-19 pandemic is very important to protect yourself and others from the risk of transmitting this virus. The aims of the study to determine the implementation of government policies regarding health protocols during the COVID-19 pandemic on the compliance of Street Vendors to using mask in Deli Tua market 2022. The type of research is a descriptive quantitative research with a cross-sectional study design. cross section). The number of available samples with 82 samples taken using accidental sampling technique. The data was collected by distributing questionnaires to 82 samples. The data analysis was carried out univariate and bivariate using Chi Square test. The results of the Chi Square test show that there is a significant relationship between the implementation of health protocols and compliance to using mask the Street Vendors in the market with a p value of 0.024<0.05. The suggestions to the perpetrators to be willing and able to implement and comply with the protocols that already exist will provide benefits for reducing transmission of the covid-19 virus and also for traders to advise buyers to comply with health protocols to jointly break the chain of transmission of the 19 virus.